2014
DOI: 10.1371/journal.pone.0103368
|View full text |Cite
|
Sign up to set email alerts
|

Habitual Functional Electrical Stimulation Therapy Improves Gait Kinematics and Walking Performance, but Not Patient-Reported Functional Outcomes, of People with Multiple Sclerosis who Present with Foot-Drop

Abstract: BackgroundPeople with Multiple Sclerosis (pwMS) often experience a disturbed gait function such as foot-drop. The objective of this pilot study was to investigate the medium term effects of using Functional Electrical Stimulation (FES) to treat foot-drop over a period 12 weeks on gait and patient reported outcomes of pwMS.Methods and FindingsNine pwMS aged 35 to 64 (2 males, 7 females) were assessed on four occasions; four weeks before baseline, at baseline and after six weeks and twelve weeks of FES use. Join… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 32 publications
3
50
1
Order By: Relevance
“…The present data suggests that for people with MS who walk faster than 0.8m/s the benefits of FES on walking speed and gait mechanics may require more time before changes occur due to the need to become conditioned to the stimulation and adapt their gait pattern to its action. The findings of van der Linden et al [29,32] lend support to this suggestion since their work showed positive orthotic effects of FES on walking speed, spatiotemporal parameters and kinematics of the hip, knee and ankle in groups of people with MS with mean walking speeds around 0.8 m/s but still less than that of the participants in the current study. Additionally, our own findings indicating that clinically meaningful increases in walking speed (i.e.…”
Section: Initial Orthotic Effect Of Fessupporting
confidence: 80%
See 4 more Smart Citations
“…The present data suggests that for people with MS who walk faster than 0.8m/s the benefits of FES on walking speed and gait mechanics may require more time before changes occur due to the need to become conditioned to the stimulation and adapt their gait pattern to its action. The findings of van der Linden et al [29,32] lend support to this suggestion since their work showed positive orthotic effects of FES on walking speed, spatiotemporal parameters and kinematics of the hip, knee and ankle in groups of people with MS with mean walking speeds around 0.8 m/s but still less than that of the participants in the current study. Additionally, our own findings indicating that clinically meaningful increases in walking speed (i.e.…”
Section: Initial Orthotic Effect Of Fessupporting
confidence: 80%
“…It is interesting to note that in some instances the values return to non-fatigued levels. The fact that at both the baseline and week 8 assessments there was no change in ankle angles at initial contact or during swing, as has been reported previously [29,32], may be due to our inclusion criteria whereby our participants had an EDSS score range of 3-4 and could reach at least a neutral ankle angle. While the stimulation did not significantly change the angle of the ankle during gait it is evident it had other beneficial effects on mechanics of the lower limb, including at the ankle.…”
Section: Continuing Orthotic Effect Of Fesmentioning
confidence: 55%
See 3 more Smart Citations